Financial Distress In Monitoring Company Financial Performance With Mediation Profitability - Soraya, Rima; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
Profitability mediates the company's financial performance in influencing financial distress to be the research objective. The data used are in the form of financial reports of companies in the Property and Real Estate sub-sector. on the Indonesia Stock Exchange for the 2020-2023 period . The research findings show that liquidity has a positive effect on financial distress, and partially profitability is not affected by liquidity and leverage. Financial distress is partially not affected by leverage and profitability. In the review of the indirect effects of liquidity and leverage, profitability cannot be mediated by financial distress.